Study the Acute & Sub Acute Toxicity of Ricinus cummunis Lnn. Ethanol Extract of Seed in Albino Mice - AL-Jborrey, Manal H.; Altaie, Muastafa A. K.; Al-Shahwany, Ayyad W. (International Journal of Scientific Research and Management (IJSRM), 2018)
Background: Toxicity still a global problem for the environment, agriculture and ultimately human health.Objective: In this study attempt to investigate the toxicological profile of the ethanol, extract of Ricinus cummunis after acute and sub-chronic administration to mice.Methods: In the acute toxicity study, a single administration of the extract at doses of 1000,2000,3000,4000 and 5000 mg/kg, respectively, was gave orally. Mice were observed for general behavioral changes, adverse effects and mortality up to 10 days post-treatment. In sub-acute toxicity studies, herbal extract was gave orally to mice at doses of 50 mg/kg, 100 mg/kg and 150 mg/kg for 10 days.Results: In the acute toxicity study, the mortality appeared in 2000 mg/kg and LD50 were calculated at 1100 mg/kg. In the sub-chronic toxicity the study show significant differences in body weight between the control and treated groups (p < 0.05). Histopathology of vital organ (liver & kidney) show morphological changes.Conclusions: These results demonstrate the real toxic effect of the ethanolic extract after single dose. The LD50 value is 1100 mg/kg and research indicates that successive use of the seed at the dose above (2 g/kg in human) daily for long period may cause toxic signs.Highlights: The Ricinus communis oil's has wide variety of industrial applications: as a drying oil for paints, varnishes, plastics and resins is an ingredient in numerous cosmetics. But it need to toxicity study as acute and sub-acute with observation of hematological and histopathological to be more safety  for used.